Influence of suspension’s parameters on fluctuations of the military caterpillar machine’s frame - Sergey Vladimirovich Baglaychuk (Вестник СибАДИ, 2017)
The article dwells on the theme of solving differential equations of the fluctuations of the military caterpillar machine’s frame with regard to relatedness between them on the grounds of analyzing influence of suspension’s parameters on vertical and angular fluctuations of the military caterpillar machine’s frame. The structure of formed dependencies with regard to relatedness points that full division of the equations of the fluctuations on coordinates and assessing, on this base, the evenness of the machine’s move will be incorrect, since mutual influence of vertical and angular fluctuations regarding to military caterpillar machine is considerable.